High Wolbachia Strain Diversity in a Clade of Dung Beetles Endemic to Madagascar - Miraldo, Andreia; Duplouy, Anne (Frontiers in Ecology and Evolution, 2019)
Determining the drivers of diversity is a major topic in biology. Due to its high level of micro-endemism in many taxa, Madagascar has been described as one of Earth’s biodiversity hotspot. The exceptional Malagasy biodiversity has been shown to be the result of various eco-evolutionary mechanisms that have taken place on this large island since its isolation from other landmasses. Extensive phylogenetic analyses have, for example, revealed that most of the dung beetle radiation events have arisen due to allopatric speciation, and adaptation to altitudinal and/or longitudinal gradients. But other biotic factors, that have yet to be identified, might also be at play. Wolbachia is a maternally transmitted endosymbiotic bacterium widespread in insects. The bacterium is well known for its ability to modify its host reproductive system in ways that may lead to either discordance patterns between the host mitochondrial and nuclear phylogenies, and in some cases to speciation. Here, we used the MultiLocus Sequence Typing system, to identify and characterize five Wolbachia strains infecting several species within the Nanos clypeatus dung beetle clade. We discuss the implications of these Wolbachia strains for the evolution and diversification of their dung beetle hosts in Madagascar.